Optimization of Preventive Replacement of Critical Components in the Komatsu PC2000-8 Excavator to Minimize Downtime at PT XYZ - Imam Nur Soleh; Mokh Suef (Green Publisher Indonesia, 2026)
The availability of primary loading equipment, particularly the Komatsu PC2000-8 excavator, is a key determinant of operational efficiency in open-pit mining. Failures of critical components directly affect downtime, maintenance costs, and key performance indicators, including physical availability (PA), mean time between failures (MTBF), and mean time to repair (MTTR). Current preventive maintenance practices, which largely follow generic original equipment manufacturer (OEM) replacement intervals, often fail to prevent actual breakdowns, highlighting the need to optimize preventive replacement intervals based on cost and downtime minimization. This study aims to determine the optimal preventive replacement intervals for the critical components of the Komatsu PC2000-8 excavator to minimize downtime and maintenance costs while improving equipment availability. The study employed a quantitative comparative optimization approach. Critical components were identified using a Pareto diagram based on failure frequency and cumulative downtime. Reliability analysis was performed by selecting the most appropriate time-between-failures distribution using Relyence Weibull software to estimate the distribution parameters. Reliability, hazard rate, MTBF, and cost analyses comparing preventive and corrective replacement—including spare parts, labor, supporting equipment, and lost production or contractual implications—were subsequently performed. An Age Replacement policy was then optimized to determine replacement intervals that minimized the long-run average cost per unit time while satisfying equipment availability constraints. The results indicated that the optimal preventive replacement intervals based on cost minimization were 11,545 hours for the Boom Cylinder, 16,820 hours for the Turbocharger, 7,366 hours for the Water Pump, 20,026 hours for the Final Drive, and 19,624 hours for the Radiator.